The Correlation Characteristics of Polarization Backscattering Matrix of Dense Chaff Clouds - B. Tang (Radioengineering, 2018)
This paper studied the correlation characteristics of the polarization backscattering matrix of the dense chaff cloud with uniform orientation and location distributions in circular symmetry region. Based on the theoretical analysis and numerical experiments, the correlation coefficients of the four elements in the polarization backscattering matrix are obtained, and the results indicate that the cross to co-polar correlation coefficient is still zero; and that the sum of the co-polar cross-correlation coefficient and the two times of linear depolarization ratio equals one. The results are beneficial for better understanding of the backscattering characteristics of dense chaff clouds, and are useful in the application of jamming recognition in radar electronic warfare. Numerical experiments are performed by using the method of moments.